EARNING MANAGEMENT: THE EFFECT OF FINANCIAL STABILITY, EXTERNAL MONITORING MECHANISM, OPPORTUNISTIC BEHAVIOR, AND INEFFECTIVE MONITORING - Novegia Ferdini; Nanda Fito Mela; Emrinaldi Nur DP (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study aims to determine the effect of financial stability as measured by changes in assets (ACHANGE), external monitoring mechanism (DAR) and opportunistic behavior (FCF) on earnings management. The addition of the ineffective monitoring variable as measured by the proportion of independent commissioners (BDOUT) is intended to determine whether this variable is able to moderate the effect of each variable. The research sample used is the financial data of companies belonging to the non-cyclical consumer sector. Observations were made for 2016-2020 accounting period based on purposive sampling method. The data that has been collected is then processed by using an application namely SPSS version 25. Based on the test, it was found that financial stability and external monitoring mechanisms have a positive effect on earnings management, opportunistic behavior has a negative effect and ineffective monitoring cannot be a moderating variable.